Curcumin: An effective adjunct in patients with statin‐associated muscle symptoms?. Issue 1 (22nd September 2016) - Sahebkar, Amirhossein; Saboni, Nikou; Pirro, Matteo; Banach, Maciej
Abstract: In spite of the unequivocal efficacy of statins in reducing primary and secondary cardiovascular events, the use of these drugs in a considerable number of patients is limited because of statin intolerance, mainly statin‐associated muscle symptoms (SAMS). SAMS encompass a broad spectrum of clinical presentations, including mild muscular aching and other types of myalgias, myopathy with the significant elevation of creatine kinase, and the rare but life‐threatening rhabdomyolysis. Among several pathophysiologic mechanisms of SAMS, mitochondrial dysfunction is thought to be one of the main one. Curcumin is the polyphenolic ingredient of Curcuma longa L., which has various pharmacological properties against a vast range of diseases. Curcumin has several mechanisms of actions relevant to the treatment of SAMS. These effects include the capacity to prevent and reduce delayed onset muscle soreness by blocking the nuclear factor inflammatory pathway, attenuation of muscular atrophy, enhancement of muscle fibre regeneration following injury, and analgesic and antioxidant effects. Curcumin can also increase the levels of cyclic adenosine monophosphate, which leads to an increase in the number of mitochondrial DNA duplicates in skeletal muscle cells. Finally, owing to its essential lipid‐modifying properties, curcumin might serve as an adjunct to statin therapy in patients with SAMS, allowing for effective lowering of low‐density lipoprotein cholesterol and possibly for statin dose reduction. Owing to the paucity of effective treatments, and the safety of curcumin in clinical practice, proof‐of‐concept trials are recommended to assess the potential benefit of this phytochemical in the treatment of SAMS.